Perdagangan Orang ( Human Trafficking) Dan Penegakan Hukum Di Kota Banjarmasin - Bahran Bahran (Syariah: Jurnal Hukum dan Pemikiran, 2013)
Human frafficking, particularly among the children, is offensively against a human dignity as well as human right. In Banjarmasin , recruiting the childe to become a beggar on the street is classified as a human trafficking crime. This recruitment intends, other than exploit these children, also to make people suffering for sadness and sorrow, therefore these tend to donate them some money. This ekploit indeed, is ordered as a crime which also defined by the act 21 year 2007. However the supremacy of law for the actor of this human trafficking crime in Banjarmasin is still pathetically very vulnerable.